Assessment of Keratinase and Other Hydrolytic Enzymes in Thermophilic Bacteria Isolated from Geothermal Areas in Patagonia Argentina. Issue 2 (7th February 2018) - Cavello, I.; Urbieta, M. S.; Segretin, A. B.; Giaveno, A.; Cavalitto, S.; Donati, E. R.
ABSTRACT: Thermophilic aerobic bacteria were isolated from two geothermal areas in Neuquén province using two different enrichment methods and a total of 30 isolates were obtained. From chicken feather enrichment cultures, strains affiliated to Bacillus cytotoxicus and Bacillus licheniformis were isolated and all of them demonstrated the capability to degrade completely chicken feather. A preliminary research on biotechnological enzymes' potential demonstrated that all the isolates displayed at least one of the extracellular hydrolytic enzymes tested. Most of the isolates showed protease, inulinase and/or pectinase activities, while cellulase and xylanase activities were less common. In light of these findings, geothermal areas of Argentina may be considered as a potential source of thermophilic bacteria able to produce many industrially relevant enzymes.